APA HUBUNGAN PANCASILA DAN KEBIJAKAN PUBLIK? - Xaverius Chandra (Arete, 2022)
The quote of Mohammad Hatta's statment should have triggered Indonesians to reflect on whether the Indonesian state was based on Pancasila if the 1945 Constitution was used? If the implementation of the constitution is related to public policy, should public policy in Indonesia be based on Pancasila? What is the basis of the Pancasila underlying public policies in Indonesia? Is that because Pancasila is the basis of the state so that it also underlies public policy in Indonesia? So, if Pancasila underlies public policy, what does it mean to base it here? Can Pancasila undrlie public policy? These are the questions from this essay.Key words: Pancasila, Pbulic Policy